Marketised forensic science provision in England & Wales - Richmond, Karen McGregor (Emerald Publishing Limited, 2022)
This unique work of New Evidence scholarship details the development of marketised forensic science provision in the UK. It explores the impact that public policy developments have had upon the sector, re-structuring both the governance and delivery of expert scientific evidence. Using first-hand accounts drawn from empirical research, this work analyses the practices and perspectives of forensic experts and criminal justice personnel, with a particular focus on the influence of standardisation, expertise, regulation, and scientific method. It expands our understandings of the ways in which forensic scientists have responded to policy-driven structural changes, and highlights the effects of resulting adaptations. Challenging subsisting theories of law's deference to expert knowledge, this work uncovers the normative and conceptual underpinnings of law and science, in order to provide an innovative account of the practice of case construction. Using novel methods, it endeavours to achieve a genuine theoretical engagement between the two domains, and supports this endeavour with a range of empirically informed discussions, and detailed theoretical analyses. Revisiting the landmark cases relevant legislative provisions, and government reports, it offers a trenchant analysis of law's mutable understandings of expertise and scientific method. In so doing, it lays the foundations for a more rational and systematic approach to the consumption of expert evidence.